Low-dose cisplatin exposure and SNAIL, Vimentin, E-cadherin expression in HEPG2 cell line (International Journal of Medical and Surgical Sciences, 2022)
Cisplatin, the first platinum compound approved for cancer treatment, is widely used in the treatment of various cancers including hepatocellular carcinoma (HCC). HCC incidence rates rise globally. Epithelial mesenchymal transition (EMT) is implicated in cancer invasion and metastasis, which are associated with increased mortality. Cisplatin dose might influence cancer invasion and metastatic behavior of the cells. The aim of the study was to investigate the effect of low-dose cisplatin treatment on EMT- related changes in HepG2 cells. Following treatment with 4 µM cisplatin, HepG2 cells were evaluated morphologically. Gene expression of E-cadherin, Vimentin, Snail1 was assessed by quantitative PCR. Immunofluorescence analyses of NA-K ATPase were performed. Although the low-dose cisplatin treated cells exhibited a more stretched morphology, no statistical difference was detected in gene expression of E-cadherin, Vimentin, Snail1 and immunofluorescence of NA-K ATPase. Findings on low-dose cisplatin effects in HepG2 might contribute to the knowledge of antineoplastic inefficacy by further understanding the molecular mechanisms of drug action.
Keywords: cisplatin; SNAIL; Vimentin; E-cadherin; Epithelial mesenchymal transition